Urtica dioica (Stinging Nettle): A Neglected Plant With Emerging Growth Promoter/Immunostimulant Properties for Farmed Fish - De Vico, Gionata; Guida, Vincenzo; Carella, Francesca (Frontiers in Physiology, 2018)
Urtica dioica (stinging nettle), is a perennial plant belonging to the family of Urticaceae, genus Urtica. Despite the use of nettle in folk veterinary medicine is well documented, U. dioica is today an underestimated and frequently neglected plant, considered by the contemporary agriculture as a weed to be eliminated. This mini review focus on very recent studies on dietary administration of U. dioica, both as a single herb or in combination with other herbs, to enhance growth and stimulate farmed fish immunity, thus enabling the fish to be more resistant against bacterial infections. Such an emerging feature, together with cost-effectiveness, adequate availability and easy processing of nettle, could make this herb an excellent, inexpensive and widely used dietary supplement on intensive fish farms.